2007
DOI: 10.1097/mnm.0b013e3280708edf
|View full text |Cite
|
Sign up to set email alerts
|

In search of an unknown primary tumour presenting with cervical metastases: Performance of hybrid FDG-PET–CT

Abstract: Hybrid FDG-PET-CT is helpful for the detection of a potential head and neck primary tumour. Furthermore, hybrid FDG-PET-CT has the ability to diagnose occult or distant second tumour and metastatic disease and modify patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
44
1
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 20 publications
1
44
1
3
Order By: Relevance
“…Four studies have previously reported on the therapeutic impact of FDG-PET/CT in CUP patients. [27][28][29][30] In these studies, FDG-PET/CT modified therapy in 18.2%-60% of patients. For instance, in the series by Fakhry et al in 4 patients in whom FDG-PET/CT identified the primary tumor, the size of the radiation fields could be reduced and thus also morbidity.…”
mentioning
confidence: 99%
“…Four studies have previously reported on the therapeutic impact of FDG-PET/CT in CUP patients. [27][28][29][30] In these studies, FDG-PET/CT modified therapy in 18.2%-60% of patients. For instance, in the series by Fakhry et al in 4 patients in whom FDG-PET/CT identified the primary tumor, the size of the radiation fields could be reduced and thus also morbidity.…”
mentioning
confidence: 99%
“…bilateral tonsillectomies, additional pharyngeal mucosa field irradiation). 17 PET/ CT can identify approximately 30% [18][19][20][21][22][23][24] of tumours in patients presenting cervical lymph node metastases from UPC, in whom the primary was not detected by the comprehensive diagnostic work-up including endoscopy and conventional imaging methods (CT or MRI). Table 1 summarizes the diagnostic performance of PET/CT in these studies.…”
Section: Mandibular Invasionmentioning
confidence: 99%
“…Table 1 summarizes the diagnostic performance of PET/CT in these studies. [18][19][20][21][22][23][24][25][26][27][28][29][30] It is noteworthy that it should be performed before examination under anaesthesia for targeted panendoscopy and biopsy, avoiding potential false positives due to the inflammation that usually follows these kinds of procedures. 26 Thus, a rigorous physical examination is still essential, considering that small and superficial tumours may not have enough 18 F-FDG avidity to be detected by PET/CT, as showed by Thiagarajan 5 and Daisne et al 31 Recently, Zhu et al 32 performed a meta-analysis analyzing a total of 7 studies (246 patients).…”
Section: Mandibular Invasionmentioning
confidence: 99%
“…5 Early detection of subclinical lesions can be achieved with CT or MRI, especially in patients at an advanced stage. 6 Positron emission tomography (PET) with 18 F-fluorodeoxyglucose ( 18 F-FDG) is also widely used in oncology, and is particularly useful for head and neck cancer staging, 7 detection of simultaneous cancers in different organs, 8 detection of an unknown primary tumor presenting with cervical metastases, 9 assessment of chemotherapy response, 10 and prediction of survival. 11,12 The 18 F-FDG PET/CT is also important in posttreatment surveillance of HNSCC [13][14][15][16][17][18][19] because it can distinguish recurrent HNSCC from posttreatment changes and is more effective for detection of recurrent tumors than physical examination, CT, or MRI.…”
Section: Introductionmentioning
confidence: 99%